The Functional Orlicz Brunn-Minkowski Inequality for q-Capacity - Wei Wang; Juan Li; Rigao He; Lijuan Liu (Journal of Function Spaces)
In this paper, we establish functional forms of the Orlicz Brunn-Minkowski inequality and the Orlicz-Minkowski inequality for the electrostatic q-capacity, which generalize previous results by Zou and Xiong. We also show that these two inequalities are equivalent.